Оцінка успішності інтродукції видів кавказької флори в умовах Національного ботанічного саду імені М.М. Гришка НАН України - Didenko, S.Ja. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Since 1949, when it was laid botanical-geographical plot “Caucasus”, species composition replenished through research expedition S.S. Kharkevich. Since then many years have passed. Not all of species have survived. Many species form a population of introduction. The behavior of some species has a fluctuating character. Some species, for various reasons remained small. Therefore, collection of plant species of Caucasus flora requires careful study and find ways to support new species in terms of Kyiv. The results of the introduction of herbaceous plants of the flora of the Caucasus in botanical and geographical plot “Caucasus” and evaluated its performance. Updated work to replenish the collection with new species.